PROKESOS PENANGGULANGAN KERUSUHAN KOLEKTIF - Manik Wisnu Wardhana (Politeknik Kesejahteraan Sosial, 2003)
(Social Welfare Program for Conflict Resolution).Interest conflict on many lives domein rooted collective riots problem complexities, under proportional and systimatic assesments showed interests integration point with problematic priorities of collective senses for the entry point problem solving. This developmental analization to recommend social welfare approach on viewing this problematic realities either as social potensial and recources for internal community capacities improvement through social solidarity actualization on flexible inplementation and primordialism tendention controlling and managing.Key words : Social conflic, collective riot, and social welfare approach.